Digesting the safety effectiveness of cable barrier systems by numbers. (January 2017) - Chimba, Deo; Ruhazwe, Evarist; Allen, Steve; Waters, Jim
Abstract: This paper presents median cable barrier safety effectiveness by numbers as experienced on Tennessee highways. Apart from descriptive statistics and parametric tests, before and after statistical evaluation utilizing Empirical Bayes (EB) was used to estimate the cable barriers Safety Effectiveness. The findings from the descriptive statistics, paired t -test and EB evaluation were very similar which reinforces the positive safety effectiveness performances of the cable barriers in Tennessee. The study found that the statewide cable barriers Safety Effectiveness (statistical percentage change in crash frequency across all statewide cable barrier segments) for fatal crashes is 94%, incapacitating injury crashes is 92% and fatal and incapacitating injury crashes combined is also 92%. The safety effectiveness for fatal and all injury crashes combined was found to be 85%. In a direct comparison through descriptive statistics, statewide fatal crashes were reduced by 82% after the cable barriers installation while the incapacitating injury crashes were reduced by 76%. In addition, head-on crashes went down by 96% and crashes involving two or more vehicles went down by 92%. Fatalities due to median crossover crashes were reduced by 83% while number of people injured went down by 71% as a result of cable barriers. Through modeling, wider cable offsets and inside shoulders were found to help reduce number of median related crashes while high differential elevations and high posted speed limit segments significantly had higher number of crashes compared to the opposite features. The findings can be used by state transportation agencies as a decision tool when considering installation of median cable barriers as well in determination geometry and traffic factors that play role in enhancing or worsening performance of the median cable barriers.